2003
DOI: 10.4269/ajtmh.2003.68.557
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reactivation of Human Immunodeficiency Virus-1 Upon Stimulation With Scrub Typhus Rickettsial Infection

Abstract: Abstract. While a number of microbial infections induce a transient burst in viral load in individuals infected with human immunodeficiency virus-1 (HIV-1), a recent study has suggested that scrub typhus may suppress HIV-1 infection. We investigated the effects of Orientia tsutsugamushi on HIV-1 infection. In vitro HIV-1 infection experiments were conducted using peripheral blood mononuclear cells (PBMC) acutely infected with R5 and X4 HIV-1 or PBMC derived from patients receiving highly active antiretroviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Studies have shown HIV patients infected with Orientia tsutsugamushi (bacterium that causes scrub typhus) [66, 67] or Hepatitis G/GB virus C [68, 69] have reduced viral loads and/or higher CD4 T cell counts. In vitro stimulation of PBMC with either pathogen increased secretion of RANTES [70, 71]. Although we found STLV-1 status had no impact on the outcome of SIVmac infection in baboon PBMC, protection from SIV may be elicited by other infections currently endemic in wild and captive baboon colonies.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have shown HIV patients infected with Orientia tsutsugamushi (bacterium that causes scrub typhus) [66, 67] or Hepatitis G/GB virus C [68, 69] have reduced viral loads and/or higher CD4 T cell counts. In vitro stimulation of PBMC with either pathogen increased secretion of RANTES [70, 71]. Although we found STLV-1 status had no impact on the outcome of SIVmac infection in baboon PBMC, protection from SIV may be elicited by other infections currently endemic in wild and captive baboon colonies.…”
Section: Discussionmentioning
confidence: 88%
“…Some persons who are simultaneously infected with HIV-1 and either dengue, Orienta tsutsugamushi, hepatitis G/GB virus C, or measles morbilli virus have reduced viral loads compared with patients who are infected with HIV-1 alone or with HIV-1 and other pathogens. [17][18][19][20][21][22][23][24][25] In the case of hepatitis G virus (HGV), the mechanism of action is postulated to be via binding of the serum HGV E2 protein to CD81, leading to increased regulated on activation normal T expressed and secreted protein (RANTES) secretion and reduced CCR5 expression. 24 In vitro studies have shown that HTLV-type 2 infection might up-regulate the production of macrophage inflammatory protein-1␣ (MIP-1␣).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of scrub typhus is based on the patient's history of exposure, clinical symptoms, and results of serologic testing. A high degree of clinical suspicion and familiarity with the various radiologic manifestations of scrub typhus allows early diagnosis and timely initiation of appropriate therapy and, as such, may help reduce patient morbidity and mortality (Moriuchi, Tamura, & Moriuchi, 2003; Tsay & Chang, 1998).…”
Section: Clinical Course Of Diseasementioning
confidence: 99%